Effect of Animated Video Media on Smoking Behavior Students in Junior High School Muhammadiyah 1 Purbolinggo Kabupaten Lampung Timur - Fathoni, Afriada Noor; Annisa (RADINKA JAYA UTAMA PUBLISHER, 2024)
Based on data from Purbolinggo Health Center, there was an increase in smoking among teenagers by 75.5%, At Junior High School Muhammadiyah 1 Purbolinggo, 60% of students were actively smoking. The purpose of this research is to determine the effect of animated video media on smoking behavior among students at Junior High School Muhammadiyah 1 Purbolinggo. The research design used is pre-experimental, with an approach of pretest-postest. The sample for research is 25 students. The analysis used was univariate, and bivariate analysis used a t-dependent statistical test (paired t-test). The results of the statistical test of the dependent t-test (paired t-test) obtained a P value of 0.00 < 0.05, which means that there is a significant change in behavior, knowledge, and attitude. Animation video media has a significant influence on changes in behavior, knowledge, and attitudes. Therefore, animated video media is quite effective as a medium for health promotion about the dangers of smoking in students.